Kesadaran Moral VS Pengawasan: Faktor apa yang dapat mengurangi Manajemen Laba? - Nada Yolanda; Astrid Rudyanto (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
As earnings management is management’s opportunistic behavior, board of commissioner is looking for ways to reduce earnings management, whether by increasing director’s moral awareness or monitoring of financial statement. The purpose of this study is to examine effect of moral awareness (disclosing corporate social responsibility) and monitoring (audit firm size, audit industry specialization, audit tenure) on earnings management. Using purposive sampling, this study used 77 samples (231 data) of manufacture companies listed in Indonesia Stock Exchange (BEI) during 2017-2019. Data analysis model used in this study is fixed effect panel multiple regression model. The results show that only corporate social responsibility disclosure which has negative effects on earnings management. It can be implied that moral awareness is more effective to reduce earnings management than monitoring of financial statement.